Active video games as a form of exercise and the effect of gaming experience: a preliminary study in healthy young adults. - Forde, Cuisle (My University, 2012)
Objectives: To examine the energy expenditure and heart rate response while playing active video games, and the effect of gaming experience on energy expenditure. Design: Cross-sectional study. Participants and interventions: Twenty-eight healthy participants (18 male, age 19 to 27 years) played either Wii Sports Boxing, Tennis and Baseball, or Wii Sports Boxing and Wii Fit Free Jogging. Main outcome measures: Percentage maximal heart rate (%HRmax) and metabolic equivalents (METs) were measured during 15 minutes of rest and during each game. Results: Mean %HRmax and METs while playing each of the four games were as follows: Wii Fit Free Jogging 71% [standard deviation (SD) 13%], 5.9 (SD 1.8); Wii Sports Boxing 58% (SD 13%), 3.2 (SD 1.1); Wii Sports Baseball 42% (SD 6%), 2.0 (SD 0.5); and Wii Sports Tennis 42% (SD 7%), 2.0 (SD 0.4). Subjects with gaming experience achieved a lower heart rate playing Wii Sports Tennis compared with subjects without gaming experience. Conclusions: Wii Sports Boxing, Tennis and Baseball are light-intensity activities, and Wii Fit Free Jogging is a moderate-intensity activity. Experience of gaming may affect the exercise intensity of games requiring controller skill.
PUBLISHED
Keywords: Creative Technologies; Genes & Society; EXERCISE; PAEDIATRICS; PHYSICAL ACTIVITY; PHYSICAL EXERCISE